1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Question about a cancellation law

  1. Dec 12, 2012 #1
    1. The problem statement, all variables and given/known data
    if ba = bc and a is nonzero then b = c

    3. The attempt at a solution
    if a is nonzero I can multiply both sides by a-1 to get
    ba(a-1) = bc(a-1)
    b(1) = bc(a-1)
    b = bc(a-1)
    not sure how to proceed, is the problem statement ba = bc supposed to be ab = ac ?
  2. jcsd
  3. Dec 12, 2012 #2
  4. Dec 12, 2012 #3
    i'll check it out, thanks a lot.
  5. Dec 12, 2012 #4


    User Avatar
    Homework Helper

    No, that's not true at all. For example, take b=2, a=4, c=4. The equality holds, the criteria are met, yet [itex]b\neq c[/itex]

    What you're looking for is

    If ba = bc and b is non-zero, then a = c.

    EDIT: Sorry, I missed this part:
    Yes, that's what it should be instead.
  6. Dec 12, 2012 #5


    User Avatar
    Science Advisor

    You do not say what algebraic structure you are working in. In a "cancellation ring" such as the set of all integers, with ordinary addition and multiplication as operations, we do NOT have "multiplicative inverses" but the cancellation law is still true: if ab= ac and a is not the additive identity, 0, then b= c.
  7. Dec 12, 2012 #6
    I'm not sure if this is correct, but i'm thinking it's a field since they didn't specify. My book was using this as an example of how to show that axioms that hold in real arithmetic may not hold in matrix arithmetic: "for example, consider the following two laws of real arithmetic: If ab = bc and a is nonzero then b = c. [ Cancellation Law ] "
  8. Dec 12, 2012 #7
    That so-called "cancellation law" doesn't hold for matrices. Just consider ##a=\left(\begin{array}{cc} 1&0\\0&0 \end{array}\right)## (which is nonzero), ##b=\left(\begin{array}{cc} 0&1\\1&1 \end{array}\right)## and ##c=\left(\begin{array}{cc} 0&-1\\0&1 \end{array}\right)##.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook